COGNITION AND ACHIEVEMENT IN CHILDREN WITH SEIZURE DISORDERS - Barza, Lydia (European Scientific Journal, ESJ, 2014)
School personnel can help to identify, monitor and accommodate students with seizure disorders. This article describes the general characteristics of seizure disorders and reviews research on implications for cognition and achievement among children. Despite methodological limitations of research in this area, a few trends are observed. Localization of seizure activity in the brain and age of onset have a major impact on cognition. A synthesis of major studies show that deficits often involve one or more of the following: verbal memory, visual memory, reaction time, and attention. Challenges in reading comprehension are well documented. Poor school performance, in general, may be due to frequent lapses of awareness. Recommendations are for school personnel to monitor and document symptoms at school.